VARIASI PENGGUNAAN KATA SERAPAN BAHASA DAERAH DAN BAHASA ASING PADA NOVEL â€œRANAH 3 WARNAâ€ KARYA AHMAD FUADI - kurniati, lisdwiana; Tussolekha, Rohmah; Ridayani, Ridayani (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2024)
Abstract : This research aims to describe the forms of use of variations in loanwords from regional and foreign languages through the process of adoption, adaptation and translation contained in the novel